Asymmetric and tunable infrared emission in metamaterials composed by oriented air voids into a polar material. Issue 3 (6th February 2019) - Larciprete, Maria Cristina; Centini, Marco; Li Voti, Roberto; Sibilia, Concita
ABSTRACT: We numerically investigated the asymmetric spectral emissivity in the mid- to long-infrared range of a metamaterial composed by subwavelength oriented air inclusions into a polar (SiC) matrix. The longitudinal phononic resonance can be excited and tuned as a function of the inclusions content and orientation, within the application limits of the effective medium homogenization technique. Furthermore, our numerical results show that it is possible to enhance the emissivity in a given direction rather than in the opposite one by continuously varying the inclusions filling factor along the film thickness. As an example, we design a graded air inclusion pattern starting from a few microns thick SiC layer. We show that a strongly asymmetric (forward vs. backward) emission along the normal direction to the surface can be achieved.